PID controller tuning using bacterial Quorum Sensing (QS) - Fredy Hernán Martínez Sarmiento; Diego Mauricio Acero Soto (Tecnura, 2020)
Objective: PID controllers are widely used to operate AC motors due to their simplicity and easy implementation. However, adjusting its parameters in search of an optimal scheme can be complex because it requires manual tuning by trial and error. This research aims to implement an optimized tuning scheme through a search based on the idealized behavior of a community of bacteria and its Quorum Sensing (QS).